Interaction Between the Interior Built Environment and the Human Being. an Integrative Review in Relation to Perception, Health, and Well-Being - Araya-Leon, M (Taylor and Francis Ltd., 2023)
Given that human being inhabits approximately 80% of the time within the built environment, it is necessary to understand how this affects them. Therefore, this article analyzes the state of the art on the interaction between the interior built environment and the human being, -their health and well-being- with a holistic view. Considering the perceived and not perceived aspects. And the psychological and biological responses of human beings. Through an integrative review developed at the WOS database, between 1998 and 2018 with the question: What are the parameters that have been studied of the interaction between human beings and the built environment, perceived and not perceived, related to health and well-being? and In what contexts have these issues been scientifically developed from a systemic perspective? With 11,997 titles filtered, 244 articles are analyzed. Among the main results, it is observed that the most studied context is the domestic one, followed by the work and educational context. Air quality is the most intervened parameter, followed by the physical-environmental parameters. And it is observed that matter is occasionally related to human parameters. This article proposes a vision focused on interdisciplinarity, which allows updating knowledge and contributing to evidence-based design methods. © 2022 Informa UK Limited, trading as Taylor & Francis Group.